Drug-coated balloon treatment for nonsmall de-novo coronary artery disease: angiographic and clinical outcomes. Issue 6 (18th January 2021) - Her, Ae-Young; Yuan, Song Lin; Jun, Eun Jung; Bhak, Youngjune; Kim, Moo Hyun; Garg, Scot; Kim, Yong Hoon; Kun, Liu; Hui, Lin; Zhi, Wang; Hao, Jiang; Zhentao, Shi; et al.
Abstract : Objectives: Although drug-coated balloons (DCBs) are established for de-novo lesions in small coronary arteries, the impact of DCB treatment according to the reference vessel diameter (RVD) remains poorly defined. This study aimed to evaluate the angiographic and long-term clinical outcomes of DCB treatment for de-novo coronary lesions according to RVD. Methods and results: A total of 227 patients were retrospectively enrolled and stratified according to an RVD >2.5 mm [nonsmall vessel disease (NSVD) group, n  = 100] and ≤2.5 mm [small vessel disease (SVD) group, n  = 127]. The primary endpoint was late lumen loss (LLL) at a 6-month follow-up, and the secondary endpoint was target vessel failure (TVF, a composite of cardiac death, target vessel myocardial infarction, target vessel revascularization and target vessel thrombosis). The LLL among the 206 patients (90.8%) returning for scheduled angiography at 6 month was similar (NSVD, 0.03 ± 0.22 mm vs. SVD, 0.06 ± 0.25 mm; P  = 0.384). TVF was also comparable in both groups at a median follow-up of 3.4 years (NSVD, 7.0 vs. SVD, 7.9 %; P  = 0.596). At baseline, there were numerically more dissections in the SVD group compared to the NSVD group (47.2 vs. 35.0 %; P  = 0.064); however, most of these had disappeared in both groups at a 6-month follow-up. In a multivariable analysis, the presence of dissection was not associated with LLL or TVF in either group. Conclusions: The safety and efficacy of DCB treatment for de-novo coronary lesions, in terms of LLL and TVF, was unrelated to RVD.